Youth education: maintenance the people in the field - Lima, Allison Ferreira de; Fonseca, Priscila Hilário; Firmino, Salenilda Soares; Oliveira, Jéssica Taiomara Moura Costa Bezerra de; Almeida, Eduardo Duarte de; Lima, Thyarlon Bergson Chaves; Miranda, Maria Vivianne Freitas Gomes de; Lima, Patrícia de Oliveira (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">This study aimed to provide new knowledge for livestock activities prevalent in family units through the training of students from rural schools. The learning was through a multidisciplinary team, which was part of the educational program of technical training of rural youth, entitled: "Youth Empowerment: Maintenance the people in the field", responsible for disseminating technologies through courses and practical training. This project was carried out in 55 municipal and state schools in Rio Grande do Norte State, Brazil, involving 19 municipalities and 1242 students from rural areas. The educational content of the theoretical segment had the following themes: food, health and reproductive management of cattle, goats, sheep and hens. It was noticed significant absorption of mainly content taught in the following topics: caring for the foal (87.76%), importance of castration (91.4%) and handling facilities (96.48%), respectively to the management of cattle, goat, sheep and hens. The higher performance of students among the topics discussed was the management of hens, possibly due to their wider dissemination in the region. The work achieved its goal of imparting knowledge to students, once implemented, will enable a subsequent increase in production by opening new income opportunities for small farmers and improving the economic development of families. Thus, the project has achieved the goals and provided to students from rural areas of the covered municipalities, a working knowledge of increment to be readily adopted in their production systems with real gains in health and management of cattle, goats, sheep and hens.